Lanthanide‐based bulky counterions against aggregation‐caused quenching of dyes in fluorescent polymeric nanoparticles. Issue 1 (21st October 2021) - Severi, Caterina; Lahtinen, Satu; Rosenberg, Jaana; Reisch, Andreas; Soukka, Tero; Klymchenko, Andrey S.
Abstract: Dye‐loaded polymeric nanoparticles (NPs) are promising bioimaging agents because of their available surface chemistry, high brightness, and tunable optical properties. However, high dye loadings can cause the aggregation‐caused quenching (ACQ) of the encapsulated fluorophores. Previously, we proposed to mitigate the ACQ inside polymeric NPs by insulating cationic dyes with bulky hydrophobic counterions. In order to implement new functionalities into dye‐loaded NPs, here, we extend the concept of bulky counterions to anionic lanthanide‐based complexes. We show that by employing Gd‐based counterions with octadecyl rhodamine B loaded NPs at 30 wt% versus polymer, the fluorescence quantum yield can be increased to 10‐fold (to 0.34). Moreover, Gd‐anion provides NPs with enhanced contrast in electron microscopy. A combination of a luminescent Eu‐based counterion with a far‐red to near‐infrared cyanine 5 dye (DiD) yields Forster resonance energy transfer NPs, where the UV‐excited Eu‐based counterion transfers energy to DiD, generating delayed fluorescence and large stokes shift of ∼340 nm. Cellular studies reveal low cytotoxicity of NPs and their capacity to internalize without detectable dye leakage, in contrast to leaky NPs with small counterions. Our findings show that the aggregation behavior of cationic dyes in the polymeric NPs can be controlled by bulky lanthanide anions, which will help in developing bright luminescent multifunctional nanomaterials. Abstract : Dye‐loaded polymeric nanoparticles are powerful bioimaging tools thanks to their strong brightness and biocompatibility. Here, we show that bulky hydrophobic counterions based on lanthanide complexes prevent aggregation‐caused quenching of cationic rhodamine dye inside polymeric nanoparticles. The obtained nanoparticles display high brightness, delayed fluorescence, enhanced contrast in electron microscopy, and stability against dye leakage in live cells.